Uji Antipiretik Patch Ekstrak Etanol Bawang Merah (Allium ascalonicum L.) dengan Matriks Kitosan dan Enhancer SPAN-80 terhadap Temperatur dan Jumlah Makrofag pada Tikus Putih - Kariyaningtias, Vivi; Hamid, Iwan Sahrial; Widodo, Teguh (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
Traditional medicine can be used to treat various diseases, one of which is onion (Allium ascalonicum L.) as an antipyretic agent. In this study, the antipyretic potency of ethanol extract of onion (Allium ascalonicum L.) was tested using chitosan and Span-80 as enhancer matrix with temperature and number of intraperitoneal macrophages in white rats as parameters. This study used 20 male white rats Wistar that were induced with DPTHb vaccine intraperitoneally and then divided into four groups namely positive control group (paracetamol), negative control (placebo without extract and without enhancer), formulation 1 (with extract and without enhancer), and formulation 2 (with extracts and enhancers). The results were analyzed using One Way Anova and if the results were significant, then the test continued with Duncan 5%. Correlation calculations were used to determine the relationship between temperature reduction and total intraperitoneal macrophages. The results showed that the temperature reduction did not provide a significant difference between the positive control (paracetamol) and formulation 2 (with extracts and enhancers), whereas in the negative control (without extract and without enhancer) there was no significant difference with formulation 1 (with extract and without enhancers). The total results of intraperitoneal macrophages were significantly different in all groups with a significant> 0.05.